The doorbell rang - Hutchins, Pat, 1942- (New York : Greenwillow Books, 1986)
Each time the doorbell rings, there are more people who have come to share Ma's wonderful cookies.
Elem. School Library Collection.
Notable/Best Books (A.L.A.).
Wilson's Children.
2.5
K-3
Keywords: Cookies -- Fiction; Friendship -- Fiction; Cookies -- Fiction; Friendship -- Fiction